Seasonality of calving amongst unimproved cattle in Swaziland - Butterworth, M.H. (1983)
Analyszes the seasonal distribution of calving dates using dip-tank, records of cattle of the indigenous, unimproved Nguni breed in the highweld, middleveld & lowveld ecological regions of Swaziland. Discusses these findings in the context ofd nutritional characteristics of the forage available & rainfall patterns.